Anatomical studies on two species of Dracaena in southeastern Nigeria - Ilodibia, Chinyere; Ugwu, Rachael.; Okeke, Clement; Akachukwu, Ebere; Aziagba, Bibian; Okeke, Nneka (International Journal of Biological Research, 2014)
Anatomical studies of transverse, tangential and radial longitudinal sections of roots, stems and leaves of two species of Dracaena present in southeastern Nigeria were investigated, to determine their anatomical features with regards to arrangement of vascular bundles in their roots, stems and leaves and type of secondary growth occurring in them using standard method. T- test was used for the analyses. Result showed that the number of vascular bundles in the leaves and roots of D. arborea are more in number than those of D. mannii but the reverse is the case in the stem. Secondary growth occurs in both D. mannii and D. arborea. The overall analyses showed no significant statistical difference in the anatomy of the two Dracaena species. The implication is that the two species are closely related and this justified their placement under the same genus Dracaena while the slight differences between them suggest the reason for their separation into different species.